1996
DOI: 10.1046/j.1365-2249.1996.d01-838.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human lung surfactant proteins A and D with mite (Dermatophagoides pteronyssinus) allergens

Abstract: SUMMARYHuman lung surfactant proteins A (SP-A) and D (SP-D) are both collagenous C-type lectins which appear to mediate antimicrobial activity by binding to carbohydrates on micro-organisms and to receptors on phagocytic cells. Purified native SP-A and SP-D, isolated from human bronchoalveolar lavage fluid, were found to bind to whole mite extracts (Dermatophagoides pteronyssinus) and the purified allergen Der p I, in a carbohydrate-specific and calcium-dependent manner. Binding was inhibited by ethylenediamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
85
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(87 citation statements)
references
References 25 publications
2
85
0
Order By: Relevance
“…It is plausible that many of the protective, anti-allergic effects of collectins seen in vitro and in vivo are mediated through interactions with the allergens themselves (15)(16)(17)(18)(19). To determine whether the collectins could bind to the allergens within the lung environment, solid phase binding assays were performed in BALF, which contains lipids and competitor proteins that would normally be present in the lung environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is plausible that many of the protective, anti-allergic effects of collectins seen in vitro and in vivo are mediated through interactions with the allergens themselves (15)(16)(17)(18)(19). To determine whether the collectins could bind to the allergens within the lung environment, solid phase binding assays were performed in BALF, which contains lipids and competitor proteins that would normally be present in the lung environment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated interactions between lung collectins and Der p allergens (18), but these assays were carried out in BALF to determine whether the interactions could take place in the presence of competitor proteins and lipids that would normally be present in the lung environment. NhSP-D, NhSP-A, and rfhSP-D all bound to Der p 1 and Der f 1 in a dose-dependent manner.…”
Section: Interaction Between Collectins and House Dust Mite Allergensmentioning
confidence: 99%
See 1 more Smart Citation
“…SP-A and SP-D can bind via their lectin domains to allergenic extracts derived from pollens, the house dust mite, and Aspergillus fumigatus (Afu) inhibit specific IgE binding to allergens, and block allergen-induced histamine release from sensitized basophils (15)(16)(17). SP-A and SP-D can reduce the proliferation of PBMC isolated from mite-sensitive asthmatic children (18), and SP-D, in particular, has a suppressive effect on the secretions of IL-2 by PBMC (19).…”
mentioning
confidence: 99%
“…binding of allergen-specific IgE to mite allergens (9), suggesting that these surfactant proteins may be involved in modulating allergic reactions.…”
mentioning
confidence: 99%